PERBANDINGAN SATO IMO DAN TEPUNG TERIGU DALAM PENGOLAHAN MIE SATO IMO DENGAN FORTIVIKASI KLOROFIL - Riswan Mulyadi; Andwini Prasetya; Lina Widawati (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2014)
Sato Imo, or Taro Japanese are tubers which can be processed into food products one of which was noodle. To make the noodles “Sato Imo”, Sato lmo first steamed , smoothing is done , mixing , molding and cooking . The purpose of this study was to determine the effect of comparison Sato lmo and wheat flour in making noodles Sato lmo with the addition of spinach extract on the level of consumer preference parameters based on the color , flavor , and firmness of noodles Sato lmo. The processing is done in the Mie Sato Imo the 3 treatment comparisons Sato Imo and wheat flour : 200 grams : 800 grams , 300 grams : 700 grams , 400 grams : 600 grams. The analysis conducted in this study is the organoleptic analysis. From the results of organoleptic test showed that the noodles Sato lmo most preferred in terms of color parameters , namely the treatment comparison Sato Imo and wheat flour 200 grams : 800gr with a value of 1.81 ( likes ). For a sense of the parameters of the treatment comparison Sato Imo and 400 grams of wheat flour : 600 grams with a value of 2.21 ( likes ) . For the elasticity parameter panelists preferred the noodles with comparison Sato Sato Imo Imo and 400 grams of wheat flour : 600 grams with a value of 2.37 ( likes ). Keywords : Sato Imo , Mie Sato Imo , Organoleptic Test